Javalis (Sus scrofa) são reservatórios de Leptospira interrogans no Uruguai (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2019)
Zoonotic pathogens from wildlife represent the most significant source of emerging infectious diseases. The population of wild boars, an invasive and destructive species, has increased substantially in Uruguay over the last decades, and recreational hunting of these animals is allowed since 1996. Wild boars are susceptible to leptospirosis; however it is not known whether they act as Leptospira spp. reservoirs in Uruguay.